Desenvolvimento e caracterização de cookie sem glúten enriquecido com extrato e microencapsulados de própolis vermelha - Nascimento, Natalia Miranda do (2018)
According to Anvisa Resolution RDC No. 263 of September 2005, cookies are the products obtained by mixing flour, starch (s) or starch (s) with other ingredients, submitted to kneading and baking processes, whether or not fermented. The term cookie is used in the United States and can be considered as synonymous with cookie. The addition of bioactive compounds such as red propolis to these cookies has the purpose of implementing the formulation in functional terms since propolis has been used by man due to its properties such as antimicrobial, anti-inflammatory, healing, anesthetic and antioxidant. However, the application of propolis in food is still limited because it is extracted in the alcoholic medium and present a marked flavor and aroma in this way microencapsulation becomes a way to create a barrier in this active principle and try to mask it in the food. The objective of this research was to develop gluten-free cookie formulations, based on sweet potato starch and rice flour, enriched with PV extract with concentrations of 0.05%, 0.10%, 0.20% and 0.25 % and cookies with PV microcapsules with these same concentrations. Sensory analysis was done in all these formulations with both extract and with microcapsules of PV and in the control formulation. The control formulation and cookies enriched with 0.10% EPV and cookies with MCPV at 0.20% were accepted with an acceptability index above 70% and were those that presented a higher concentration of the bioactive compound, in this way these samples were stored for the study of the stability of the antioxidant activity for 35 days and were in the first moment the analysis of water content, lipid, proteins, ashes, carbohydrates, caloric value, ABTS, DPPH, total phenolics, thermotolerant coliforms, coagulase positive staphylococci and characterization the physical. Before the sensorial analysis, none of the cookies presented microbial growth. The chitosan microcapsule collaborated with the masking of the propolis taste. The parameters of moisture, protein, lipids and caloric value did not show any significant difference between them. There were differences among the results of the physical characterization of the cookies between the samples before and after the delivery. The color of the cookies tended to red. During the 35 days of storage there was a degradation of the antioxidant compounds, however, they still presented significant values. In this way, it was concluded that it is feasible the elaboration of cookie enriched with extract and microcapsules of red propolis.